Intra- and interspecific analysis of first instar larval morphology in the genus Berberomeloe Bologna 1989 (Coleoptera: Meloidae) - Settanni, Chiara; Giulio, Andrea Di; Finoia, Maria Grazia; Bologna, Marco A. (Zootaxa, 2009)
The first instar larva of Berberomeloe insignis (Charpentier, 1818) is described and figured for the first time and compared to that of B. majalis (Linnaeus, 1758). Diagnostic larval characters of the genus and of both species are identified. Morphometric data from different populations are analyzed statistically. Results support species differentiation and characters definition. Additionally, analyses also suggest that whereas B. majalis is structured in the Iberian Peninsula, there is a lack of differentiation between Iberian and North African populations.